Inverse pH Gradient-Assay for Facile Characterization of Proton-Antiporters in Xenopus Oocytes - Zeinu Mussa Belew; Christa Kanstrup; Chengyao Hua; Christoph Crocoll; Hussam Hassan Nour-Eldin (Membranes, 2024)
Xenopus oocytes represent one of the most versatile model systems for characterizing the properties of membrane transporters. However, for studying proton-coupled antiporters, the use of Xenopus oocytes has so far been limited to so-called injection-based transport assays. In such assays, where the compound is injected directly into the oocytes’ cytosol and transport is detected by monitoring substrate efflux, poor control over internal diffusion and concentration are incompatible with mechanistic characterizations. In this study, we present an inverse pH-gradient transport assay. Herein, an outward-facing proton gradient enables the characterization of proton antiporters via facile import-based transport assays. We describe two approaches for establishing sustained outward-facing proton gradients across the oocyte membrane, namely by applying alkaline external conditions or through surprisingly stable carbonyl cyanide m-chlorophenyl-hydrazone (CCCP)-mediated acidification of the cytosol. Previously, genetic evidence has shown that DTX18 from Arabidopsis thaliana is essential for the deposition of the hydroxycinnamic acid amide p-coumaroylagmatine (coumaroylagmatine) defence compound on the leaf surface. However, direct evidence for its ability to transport coumarol-agmatine has not been provided. Here, using Xenopus oocytes as expression hosts, we demonstrate DTX18’s ability to transport coumaroyl-agmatine via both injection-based and inverse pH-gradient transport assays. Notably, by showing that DTX18 is capable of accumulating its substrate against its concentration gradient, we showcase the compatibility of the latter with mechanistic investigations.